Geochemistry of Hautasuo-Tupakkisuo HT (A1100#2) peat core from Finland - Markku Mäkilä (PANGAEA, 2021)
Geochemistry data of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.